PENERAPAN PELAYANAN PRIMA SEBAGAI UPAYA MENINGKATKAN KEPUASAN PELANGGAN DI POLITEKNIK MANUFAKTUR NEGERI BANDUNG - Emma Dwi Ariyani (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
Excellent service is one among indicators of both private and public institution performance. A productive institution is the one able to provide services in favor of its main customers or clients. The demand of excellent service is not only directed toprivate institutions but also public institution. POLMAN Bandung as a public institution always tries to upgrade its service quality in order to enhance its customers’ satisfaction.